2004
DOI: 10.1111/j.1365-2842.2004.01266.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of masticatory muscle pain on electromyographic activities of cervical muscles in patients with myogenous temporomandibular disorders

Abstract: The present study tested the hypothesis that the resting electromyographic (EMG) activities of sternocleidomastoid and trapezius muscles of myogenous temporomandibular disorder (TMD) patients would be significantly greater than healthy individuals. Eight masticatory muscle pain patients without disc interference disorders (DID) and 30 patients with DID along with 41 matched control subjects were included in the study. The resting EMG activities of sternocleidomastoid and trapezius muscles were recorded with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0
14

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 24 publications
2
52
0
14
Order By: Relevance
“…In a recent study, the authors reported association between pain in the masticatory and trapezius and sternocleidomastoideus muscles in subjects with myogenic TMD (29) . Additionally, among the cervical signs and symptoms that accompany the TMD severity, the pain during palpation of cervical muscles was the most important in this association (1) .…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, the authors reported association between pain in the masticatory and trapezius and sternocleidomastoideus muscles in subjects with myogenic TMD (29) . Additionally, among the cervical signs and symptoms that accompany the TMD severity, the pain during palpation of cervical muscles was the most important in this association (1) .…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between the stomatognathic and craniocervical systems was shown by the interplay between the masticatory and cervical muscles (5,6) . Patients with TMD, besides having pain in the craniomandibular region, also present more neck pain (7) .…”
Section: Introductionmentioning
confidence: 99%
“…Some studies (5,7,9,10) have shown that patients with TMD, compared to asymptomatic patients, showed alterations in the activity of the masticatory muscles during chewing. However, the cited studies are not conclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Isso foi necessário devido a alguns relatos na literatura da existência de diferenças na atividade EMG entre pacientes com DTM e sujeitos assintomáticos. Alguns estudos têm encontrado em pacientes com DTM quando comparados com controles assintomáticos uma menor atividade eletromiográfica em apertamento (VISSER et al, 1994;PINHO et al, 2000;CHANDU et al, 2004) e uma mais alta atividade EMG em repouso (GLAROS, PINHO et al, 2000;SUVINEN et al, 2003;CHANDU et al, 2004), e ainda tem sido relatado um aumento da atividade postural nos músculos esternocleidomastóideo e trapézio (PALLEGAMA et al, 2004).…”
Section: Discussionunclassified
“…Em um estudo, Pallegama et al (2004) observaram em pacientes com dor nos músculos mastigatórios sem desordens da ATM e em pacientes com interferencia do disco na ATM, aumento das atividades postural nos músculos esternocleidomastóideo e trapézio quando comparado com controles assintomáticos. Os autores verificaram também a presença de dor nos músculos examinados (esternocleidomastóideo e trapézio) demonstrando significante associação com DTM miogênica sem interferencias articulares.…”
Section: Eletromiografia De Superfícieunclassified